Valeriana pilosa Roots Essential Oil: Chemical Composition, Antioxidant Activities, and Molecular Docking Studies on Enzymes Involved in Redox Biological Processes - Minchán Herrera, Patricia.; Ybañez Julca, Roberto O.; Quispe Díaz, Iván M.; Venegas Casanova, Edmundo A.; Jara Aguilar, Rafael.; Salas, Felipe; Zevallos Escobar, Liz.; Yáñez Osses, Osvaldo Andrés.; Pino Ríos, Ricardo.; Buc Calderon, Pedro.; Benites, Julio (MDPI, 2022)
Valeriana pilosa is usually employed in Peruvian folk medicine in the form of infusion to treat stomach pain, and has antispasmodic, relaxing, sleep-promoting, and sedative properties, as well as is an anti-inflammatory. In this study, Valeriana pilosa essential oil (VPEO) was obtained by hydrodistillation, analyzed by GC and GC/MS, and 47 compounds were identified. Major oil components were α-patchoulene (5.8%), α-humulene (6.1%), seychellene (7.6%), and patchoulol (20.8%). Furthermore, we assessed the in vitro antioxidant activities, molecular docking, and Ligand Efficiency studies on enzymes involved in cellular redox pathways such as CYP2C9, catalase, superoxide dismutase, and xanthine oxidase. Essential oil antioxidant activities were assessed by FRAP, ABTS•+, and DPPH• radical scavenging activity. VPEO displays high antioxidant activity as compared to essential oils of Valeriana jatamansi and Valeriana officinalis oil roots. In addition, molecular docking and ADMET prediction was employed to compare the absorption, metabolism, and toxicity properties of Valeriana pilosa compounds. In the molecular docking studies, limonene, p-cimene, carvone, α-cubebene, cyclosativene, α-guaiene, allo-aromadendrene, valencene, and eremophyllene were the compounds with the best docking score on CYP2C9 and xanthine oxidase. Thus, volatile components of Valeriana pilosa could be associated with the detected antioxidant activity, acting as putative inhibitors of CYP2C9 and xanthine oxidase
Keywords: Antioxidant activities; Antioxidant enzyme; Molecular docking; Valeriana pilosa; Antioxidantes; Estrés oxidativo